FACTORS ASSOCIATED WITH PREVENTIVE BEHAVIOR OF NON-COMMUNICABLE DISEASE RISK FACTORS IN ADOLESCENT POSYANDU BINAKA VILLAGE, GUNUNGSITOLI IDANOI SUBDISTRICT IN 2023 - Telaumbanua, Natalia; Sinaga, Janno (Akupun Tour Publisher, 2023)
Background: Non-communicable diseases are the leading cause of premature death globally. Every year, 41 millions people die from heart attacks, strokes, cancer, chronic respiratory diseases, and diabetes, with a percentage of 70%. Research by Balitbangkes states that the number of non-communicable diseases in Indonesia is currently starting to be experienced by young age groups aged 10–14 years (Ministry of Health of the Republic of Indonesia, 2020). This is also supported by the results of Basic Health Research (Riskesdas) which show an increase in the prevalence of diabetes, stroke, hypertension and joint disease from 2007, 2013, to 2018. Non-communicable diseases can be prevented through changing behavior towards awareness of the importance of maintaining body health. Non-communicable diseases can be prevented through changes in mindset and behavior patterns and awareness of the importance of maintaining a healthy body. Prevention of non-communicable diseases in the community starts in adolescence and is initiated by adolescents themselves. Purpose: This study aims to determine the factors associated with the prevention behavior of non-communicable disease risk factors in the youth of Binaka Village, Gunungsitoli Idanoi District, 2023. Method: This type of research is quantitative research with an analytic or observational design using a cross-sectional approach. The study population was adolescents who were active in the Youth Posyandu of Binaka Village, Gunungsitoli Idanoi District, totaling 85 people and a sample of 46 people. The measuring instrument was a questionnaire and direct observation of all respondents. Data were analyzed using the Chi-Square. Results: The results showed that all variables were related to the prevention behavior of non-communicable disease risk factors. There is a relationship between knowledge and prevention behavior of non-communicable disease risk factors (p = 0.008); there is a relationship between family support and prevention behavior of non-communicable disease risk factors (p = 0.004); there is a relationship between peer support and prevention behavior of non-communicable disease risk factors (p = 0.016); there is a relationship between the availability of facilities and prevention behavior of non-communicable disease risk factors (p = 0.004); and there is a relationship between the role of health workers and prevention behavior of non-communicable disease risk factors (p = 0.027). Disscusion and Conclusion: It is recommended to the Head of UPTD Puskesmas Gunungsitoli Idanoi District to continue to carry out education, to adolescents to be more active in attending youth posyandu and continue to behave healthy, and to the family or community to keep motivating adolescents and creating a healthy environment, including a healthy lifestyle in the family.